APPROPRIASI TEORI KRITIS OLEH PARA PEMIKIR MUSLIM - Hendragunawan Sardjan Thayf; Muhammad Mukhtasar Syamsuddin; Supartiningsih Supartiningsih (UIN Sunan Kalijaga Yogyakarta, 2020)
Critical Theory, especially of the Frankfurt School variant, is one of the theoretical and methodological lenses used quite often by contemporary Islamic thinkers. One thinker who is explicit in his adoption and adaptation of the thinking of the Frankfurt School is Fawzia Gilani-Williams who proposes an